International Supply Chain of Bottlenecks and their Macroeconomic Implications (with Special Reference to Iraq) - Al- Faisal, Ihab; BADAN, ZAHID. (The Gulf Economist, 2024)
Abstract Supply chains play a major role in the modern international economy and represent the set of separate processes linked together to achieve the goal of delivering the final product to consumers. Digital supply chain management systems include software packages and material handling for all parties working together to create a product or service, fulfill orders, and track information, including suppliers, manufacturers, wholesalers, transportation companies, logistics providers, and retailers. The problem of supply chain bottlenecks became clear during the COVID-19 crisis, as many countries that depend on the industrial and agricultural sectors began to suffer from a shortage of supplies of raw and intermediate materials, which caused a rise in price levels. The COVID-19 crisis and the other political circumstances; like the Ukraine crisis, have affected the size of aggregate demand and the decline in the performance of economic activity, but they have contributed to changing the patterns of demand for international supply chains by reducing the demand for capital and intermediate goods and production inputs, and increasing the demand for consumer and technology products, especially through e-shopping platforms and various digital purchasing tools. The geographical location of Iraq gives it great economic importance to be a link between the continents of the world and the centers of global production and consumption in the West and East and contributes to achieving a comparative advantage that enhances the competitiveness of the Iraqi economy.